Molecular sieve boron SSZ-117x

By introducing boron into the SSZ-117x catalyst, the synthesis of boron SSZ-117x molecular sieve was solved, and the problem of lack of boron version catalyst in the prior art was achieved, and the efficient catalytic effect in the conversion reaction of organic compounds and the importance of adsorption/separation of materials was achieved. value.

CN119486970APending Publication Date: 2025-02-18CHEVRON USA INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380051170.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-31
Filing Date
2023-05-30
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing SSZ-117x catalyst does not disclose boron versions, limiting its application in organic compound conversion reactions.

Method used

A crystalline molecular sieve called boron SSZ-117x was successfully synthesized by using N,N,N,3,5-pentamethyladamantane-1-ammonium cation as a structural guide. The method includes providing a reaction mixture comprising a FAU backbone type zeolite, a germanium source, a boron source, a fluorine ion source, and water and subjecting it to crystalline crystallization conditions sufficient to form an SSZ-117x boron molecular sieve.

Benefits of technology

The unique ability as a catalyst in organic compound conversion reactions is achieved and provides important value for adsorption/separation of materials. The boron SSZ-117x catalyst exhibits efficient catalytic effects in the reforming reaction, which can significantly increase the amount of aromatic compounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005220607940000021
    Figure BDA0005220607940000021
  • Figure BDA0005220607940000031
    Figure BDA0005220607940000031
  • Figure BDA0005220607940000042
    Figure BDA0005220607940000042
Patent Text Reader

Abstract

A novel synthetic crystalline boron germanium silicate molecular sieve material is provided, named as boron SSZ-117x. The N, N, N, 3, 5-pentamethyladamantane-1-ammonium cation can be used as a structure directing agent to synthesize boron SSZ-117x. The synthesis employs a boron pathway to achieve boron molecular sieves. The boron SSZ-117x may be used in organic compound conversion reactions such as reforming and / or adsorption processes.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. Provisional Application No. 63 / 365,534, filed on May 31, 2022, the complete disclosure of which is incorporated herein by reference in its entirety. Field of the Invention

[0003] The present disclosure relates to a novel synthetic crystalline molecular sieve designated as SSZ-117x containing boron in its framework. The present disclosure also relates to its synthesis. Background of the Invention

[0005] Molecular sieves are a commercially important class of materials that have a unique crystal structure with a defined pore structure shown by a unique X-ray diffraction (XRD) pattern. Molecular sieves also have a specific chemical composition. The crystal structure defines cavities and pores that are characteristic of a specific type of molecular sieve. Providing new molecular sieves that differ in crystal structure and composition can lead to unique catalysts or adsorption / separation materials. Changing the crystal structure is always fraught with difficulty, but success can provide benefits in new catalysts for organic compound conversion reactions. U.S. Patent Publication 2022 / 0072520 discloses the preparation of SSZ-117x. However, it does not disclose boron SSZ-117x. Summary of the invention

[0006] According to the present disclosure, a crystalline molecular sieve designated as boron SSZ-117x was synthesized using N,N,N,3,5-pentamethyladamantan-1-ammonium cation as a structure directing agent (SDA). The synthesis was found to be successful in providing a boron-containing molecular sieve having the SSZ-117x crystal structure.

[0007] In one aspect, a boron SSZ-117x molecular sieve is prepared which, in its as-synthesized form, has a powder X-ray diffraction pattern comprising at least the peaks in Table 3 below.

[0008] In its as-synthesized and anhydrous form, the boron molecular sieve may have a chemical composition comprising the following molar relationship:

[0009] Table 1

[0010]

[0011] wherein T is a tetravalent element including silicon and germanium; and Q + Contains N,N,N,3,5-pentamethyladamantan-1-ammonium cation. In one embodiment, the ratio of TO2 / B2O3 is in the range of 15-20.

[0012] In its calcined or ozonated form, the boron SSZ-117x molecular sieve may have a chemical composition comprising the following molar relationship:

[0013] B2O3:(n)TO2

[0014] wherein n is ≥ 10; and T is a tetravalent element including silicon and germanium.

[0015] In another aspect, a method for synthesizing a boron SSZ-117x molecular sieve is provided. The method comprises (a) providing a reaction mixture comprising: (1) a FAU framework type zeolite; (2) a germanium source; (3) a boron source; (4) N,N,N,3,5-pentamethyladamantane-1-ammonium hydroxide (Q); (5) a fluoride ion source; and (6) water. The reaction mixture is then subjected to crystallization conditions sufficient to form crystals of the SSZ-117x boron molecular sieve. T is as described above.

[0016] The boron-containing molecular sieve is then treated to remove the structure directing agent (SDA), designated above as Q. The SDA may be removed by calcination, or by ozone treatment, for example at 150° C. It has also been found that treatment of the molecular sieve with dimethylformamide also removes SDA.

[0017] In yet another aspect, a method of converting a feedstock comprising an organic compound to a conversion product is provided, comprising contacting the feedstock with a catalyst comprising a boron SSZ-117x molecular sieve under organic compound conversion conditions.

[0018] Among other factors, the method of the present application allows technicians to obtain boron SSZ-117x molecular sieve, which is borogermanosilicate. This new molecular sieve prepared by the method of the present application provides a unique ability to act as a catalyst in organic compound conversion reactions such as reforming. Molecular sieves are also found to be of great value as adsorption / separation materials.

[0019] Details

[0020] definition

[0021] The term "framework type" has the meaning described in "Atlas of Zeolite Framework Types" by Ch. Baerlocher and LB McCusker and DH Olsen (Elsevier, 6th revised edition, 2007).

[0022] The term "boron germanosilicate" refers to a crystalline microporous solid comprising boron, germanium and silicon oxide within its framework structure. Boron germanosilicates may be "pure boron germanosilicates" (i.e., no other detectable metal oxides are present within its framework structure) or optionally substituted. When described as "optionally substituted", the corresponding framework may contain other atoms (e.g., Al, Ga, In, Fe, Ti, Zr) substituted for one or more atoms not already present in the bulk framework.

[0023] The term "as-synthesized" is used herein to refer to the molecular sieve in its form following crystallization, but prior to removal of the structure directing agent.

[0024] The term "anhydrous" is used herein to refer to molecular sieves that are substantially free of physically and chemically adsorbed water.

[0025] As used herein, the numbering scheme of the Periodic Table of the Elements is as disclosed in Chem. Eng. News 1985, 63(5), 26-27.

[0026] Synthesis of molecular sieves

[0027] The present boron molecular sieve SSZ-117x is synthesized by: (a) providing a reaction mixture comprising (1) a FAU framework type zeolite; (2) a germanium source; (3) a boron source; (4) N,N,N,3,5-pentamethyladamantane-1-ammonium hydroxide (Q); (5) a fluoride ion source; and (6) water; and then (b) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the SSZ-117x boron molecular sieve. T is as described herein above. In one embodiment, the FAU framework zeolite has only a small amount of Al2O3. The ratio of SiO2 / Al2O3 may be 300 or greater. Thus, the framework contains a large amount of boron.

[0028] The reaction mixture may have a composition in terms of molar ratios within the ranges listed in Table 2:

[0029] Table 2

[0030]

[0031]

[0032] wherein T and Q are as described herein above.

[0033] Suitable silicon oxide sources can include any suitable known sources such as colloidal silicon dioxide, fumed silica, precipitated silica or alkali metal silicate. FAU framework type zeolite such as zeolite Y can also be a silicon oxide source. In this case, the FAU framework type zeolite has at least 250 and preferably at least 300 (such as 300 to 500) very high SiO / Al O mol ratio. The FAU framework type zeolite can include two or more FAU framework type zeolites with different SiO / Al O mol ratio. The FAU framework type zeolite can be zeolite Y, or any of its various post-synthesis modified forms, as known in the art. It is most important to include boron in the final framework by the method of the application.

[0034] Germanium sources may include germanium oxide and germanium alkoxides (eg, germanium ethoxide, germanium isopropoxide), germanium hydroxide, and germanium carboxylates.

[0035] Silicon and germanium may be present in the reaction mixture in a SiO2 / GeO2 molar ratio of 4 to 12 (eg, 6 to 10).

[0036] The boron source may include boric acid, which is preferred. Other suitable sources may also be used but are not preferred.

[0037] Fluoride ion sources may include, for example, hydrogen fluoride, ammonium fluoride, and ammonium bifluoride.

[0038] SSZ-117x with boron was synthesized using a structure directing agent comprising an N,N,N,3,5-pentamethyladamantan-1-ammonium cation (Q+) represented by the following structure (1):

[0039]

[0040] The reaction mixture typically has a Q / F molar ratio in the range of 0.80 to 1.20 (eg, 0.85 to 1.15, 0.90 to 1.10, 0.95 to 1.05, or 1 to 1).

[0041] The reaction mixture may contain seeds of a molecular sieve material, such as boron SSZ-117x from a previous synthesis, in an amount of 0.01-10,000 ppm by weight (e.g., 100-5000 ppm by weight) of the reaction mixture. Seeding may be advantageous in reducing the amount of time required for complete crystallization to occur. Additionally, seeding may result in a product that is higher in purity by promoting nucleation and / or formation of boron SSZ-117x over any unwanted phases.

[0042] Note that the reaction mixture components can be supplied by more than one source. In addition, two or more reaction components can be provided by one source. The reaction mixture can be prepared in batches or continuously.

[0043] Crystallization and post-synthesis processing

[0044] The reaction mixture can be prepared under static, tumbling or stirring conditions in a suitable reactor vessel (e.g., polypropylene jars or Teflon TM The crystallization of the boron molecular sieve from the above reaction mixture is carried out in a 10-150°C-lined or stainless steel autoclave) at a temperature of 125°C-200°C (e.g., 150°C to 170°C) for a time sufficient for crystallization to occur at the temperature used (e.g., 1 day to 20 days, or 2 days to 10 days). The hydrothermal crystallization process is typically carried out under pressure, such as in an autoclave, and preferably under autogenous pressure.

[0045] Once the molecular sieve crystals containing boron are formed, the solid product can be recovered from the reaction mixture by standard mechanical separation techniques such as centrifugation or filtration. The recovered crystals are washed with water and then dried to obtain the original molecular sieve crystals of SSZ-117x boron after synthesis. The drying step can be carried out at an elevated temperature (e.g., 75° C. to 150° C.) for several hours (e.g., about 4 to 24 hours). The drying step can be carried out under vacuum or atmospheric pressure.

[0046] As a result of the crystallization process, the recovered crystallized molecular sieve product contains within its pore structure at least a portion of the structure directing agent used in its synthesis.The as-synthesized molecular sieve may be subjected to treatment to remove some or all of the structure directing agent used in its synthesis.

[0047] Removal of the structure directing agent may be performed by heat treatment (e.g., calcination), wherein the as-synthesized molecular sieve is heated at a temperature sufficient to remove some or all of the structure directing agent. Although subatmospheric pressure may be used for the heat treatment, atmospheric pressure is desired for reasons of convenience. The heat treatment may be performed at a temperature of at least 370° C. for at least one minute and typically not longer than 20 hours (e.g., 1-12 hours). The heat treatment may be performed at a temperature of up to about 925° C. For example, the heat treatment may be performed at a temperature of 400° C. to 600° C. in the presence of an oxygen-containing gas.

[0048] Additionally or alternatively, the structure directing agent can be removed by treatment with ozone. See, for example, AN Parikh et al., Micropor. Mesopor. Mater. 2004, 76, 17-22. In one embodiment, the use of ozone is preferred because it provides a higher micropore volume. It has also been found that SDA can be removed by treatment with dimethylformamide, for example at about 150°C.

[0049] Characterization of Molecular Sieve

[0050] In its as-synthesized and anhydrous form, the molecular sieve SSZ-117x with boron may have a chemical composition comprising the following molar relationships listed in Table 1:

[0051] Table 1

[0052]

[0053] Wherein T is a tetravalent element including silicon and germanium; and Q+ comprises N,N,N,3,5-pentamethyladamantan-1-ammonium cation. In some aspects, the molecular sieve may have a SiO2 / GeO2 molar ratio in the range of 4 to 12 (e.g., 6-10). In one embodiment, the SiO2 / GeO2 molar ratio is in the range of 7 to 10 and preferably about 9. In one embodiment, the ratio of TO2 / B2O3 is in the range of 15-20.

[0054] It should be noted that the as-synthesized form of the SSZ-117x molecular sieve of the present application with boron may have a molar ratio different from the molar ratio of the reactants of the reaction mixture used to prepare the as-synthesized form. This result may occur due to incomplete incorporation of 100% of the reactants of the reaction mixture into the crystals formed (from the reaction mixture).

[0055] In its calcined form, molecular sieve boron SSZ-117x may have a chemical composition comprising the following molar relationship:

[0056] B2O3:(n)TO2

[0057] wherein n is ≥ 10 (eg, 15 or greater, or in the range of 15-20); and T is a tetravalent element including silicon and germanium.

[0058] Molecular sieve boron SSZ-117x is characterized by a powder XRD pattern, which in the as-synthesized form of the molecular sieve, includes at least the peaks listed below in Table 3. In another aspect, after undergoing ozonolysis, boron SSZ-117x has a unique XRD pattern comprising at least the peaks listed below in Table 4.

[0059] Table 3 Characteristic peaks of the original boron SSZ-117x after synthesis

[0060] <![CDATA[2-θ (a) ]]> d-spacing, nm <![CDATA[Relative intensity (b) > 4.03 2.191 VS 4.54 1.943 M 8.05 1.098 W 11.65 0.759 VS 12.07 0.733 M 14.10 0.628 W 14.47 0.611 M 16.23 0.546 W 17.66 0.502 M 18.86 0.470 M 20.30 0.437 W 21.71 0.409 M

[0061] (a) ±0.30 degrees

[0062] (b) The powder XRD patterns provided are based on a relative intensity scale, where the most intense line in the X-ray pattern is assigned a value of 100: W = weak (>0 to ≤20); M = medium (>20 to ≤40); S = strong (>40 to ≤60); VS = very strong (>60 to ≤100).

[0063] Table 4 Characteristic peaks of calcined boron SSZ-117x

[0064]

[0065]

[0066] (a) ±0.30 degrees

[0067] (b) The powder XRD patterns provided are based on a relative intensity scale, where the most intense line in the X-ray pattern is assigned a value of 100: W = weak (>0 to ≤20); M = medium (>20 to ≤40); S = strong (>40 to ≤60); VS = very strong (>60 to ≤100).

[0068] As will be appreciated by those skilled in the art, the determination of the parameter 2-theta (2θ) is subject to both human and machine errors, the combination of which can impose an uncertainty of approximately ±0.30° on each reported value of 2-θ. o ) is recorded as the ratio of the peak intensity to the intensity of the strongest peak, which is assigned a value of 100. The relative intensities of the d-spacings are indicated by the notations VS, S, M, and W, which represent very strong, strong, medium, and weak, respectively. In terms of relative intensity, the above designations are defined as: W (weak) <20; M (medium) is >20 and <40; S (strong) is 40 and <60; and VS (very strong) is 60. When the intensity is near the end of the range, the intensity can be characterized as being in either range. For example, an intensity of 18-22 can be listed as WM. However, due to variations in line intensity, as is known in the art, one or more lines may have intensities in adjacent ranges.

[0069] The powder X-ray diffraction patterns presented herein were collected by standard techniques. The radiation was CuKα radiation. The peak heights and positions varied with 2θ (where θ is the Bragg angle), the relative intensities of the peaks were read (adjusted for background), and d (corresponding to the interplanar spacing of the recorded lines) could be calculated.

[0070] The slight changes in the diffraction pattern can be caused by the changes in the molar ratio of the framework material of the sample caused by the change in the lattice constant. In addition, disordered materials and / or sufficiently small crystals will affect the shape and intensity of the peak, thereby causing significant peak broadening. The slight changes in the diffraction pattern can also be caused by the changes in the organic compounds used in the preparation. Calcination can also cause slight shifts in the XRD pattern. Despite these slight disturbances, the basic lattice structure remains unchanged.

[0071] Adsorption and catalysis

[0072] The present molecular sieve boron SSZ-117x (wherein some or all of the Q+ is removed) can be used as a sorbent or as a catalyst to catalyze a variety of organic compound conversion processes. A particular application is the use of boron SSZ-117x as a catalyst in a reforming process. In one embodiment, the catalyst also contains platinum.

[0073] Catalytic reforming is one of the basic petroleum refining processes for upgrading light hydrocarbon feedstocks (often referred to as naphtha feedstocks). Products from catalytic reforming may include high-octane gasoline, aromatic compounds (e.g., benzene, toluene, xylene, and ethylbenzene) and / or hydrogen that can be used as automotive fuels. Typical reactions included in catalytic reforming include dehydrogenation cyclization, isomerization, and dehydrogenation of naphtha range hydrocarbons, dehydrogenation cyclization and dehydrogenation of linear and slightly branched alkanes, and dehydrogenation of cycloalkanes, thereby resulting in the production of aromatic compounds. Dealkylation and hydrocracking are usually undesirable due to the low value of the resulting light hydrocarbon products.

[0074] Boron SSZ-117x catalysts used in catalysts commonly used in commercial reforming reactions often include a Group VIII metal such as platinum or palladium, or a Group VIII metal plus a second catalytic metal that acts as a promoter. Examples of metals that can be used as promoters include rhenium, tin, tungsten, germanium, cobalt, nickel, rhodium, ruthenium, iridium, or a combination thereof. One or more catalytic metals can be dispersed on a carrier such as alumina, silica, or silica-alumina.

[0075] Boron SSZ-117x reforming catalyst can be used in the form of pill, particle, granule, fragment or various special shapes, arranged as fixed bed in reaction zone, and charge can be liquid phase, gas phase or mixed phase and flow through upward, downward or radially. Alternatively, reforming catalyst can be used in moving bed or fluidized solid process, wherein charge passes through the turbulent bed of finely broken catalyst upward. However, due to less catalyst loss and other operational advantages, fixed bed system or dense phase moving bed system are preferred. In fixed bed system, feed (by any suitable heating device) is preheated to the desired reaction temperature and then passed into the reaction zone of the fixed bed containing catalyst. The reaction zone can be one or more independent reactors, which have suitable devices to maintain the desired temperature at the reactor inlet. Temperature must be maintained because reforming reaction is typically endothermic in nature.

[0076] The actual reforming conditions will often depend, at least in part, on the feed used (whether highly aromatic, paraffinic, or naphthenic), and the desired octane rating of the product and the desired hydrogen production. Example

[0077] The following illustrative examples are intended to be non-limiting.

[0078] Example 1

[0079] Synthesis of N,N,N,3,5-pentamethyladamantane-1-ammonium hydroxide

[0080] 3,5-dimethyladamantan-1-amine was permethylated by treating with more than 3 times excess iodomethane and 2 equivalents of potassium bicarbonate in methanol for several days. The reaction mixture was concentrated under reduced pressure and the resulting solid was extracted twice with chloroform. The crude product was recovered by rotary evaporation of chloroform under reduced pressure. The crude product was recovered by stripping chloroform. The crude product was heated at 70°C in a minimum amount of 95% ethanol to produce a clear solution. The solution was cooled to room temperature to provide the iodide salt as very clean crystals. The purity of the product was then confirmed by both chemical analysis and H and C NMR in CDCl3.

[0081] By exchanging the resulting iodide salt with a hydroxide exchange resin ( IRN78) was stirred overnight in deionized water to exchange the resulting iodide salt for the corresponding hydroxide salt. The solution was filtered and the filtrate was analyzed for hydroxide concentration by titrating a small sample with a standard solution of 0.1N HCl.

[0082] Example 2

[0083] Synthesis of SSZ-117x with Boron

[0084] To a tared 23 mL Parr reactor, 0.27 g of Tosoh 390HUA Y-zeolite (SiO2 / Al2O3 molar ratio of about 500), 0.05 g of GeO2, 0.02 g of H3BO3, and 2.5 mmoles of N,N,N,3,5-pentamethyladamantane-1-ammonium hydroxide aqueous solution were added. The reactor was then placed in a fume hood and the water was evaporated to a H2O / (SiO2+GeO2) molar ratio of 7 (as measured by the total mass of the suspension). HF (2.5 mmoles) was then added and the reactor was heated to 160°C while tumbling at 43 rpm for about 7 days. The solid product was recovered by centrifugation, washing with deionized water, and drying at 95°C.

[0085] Powder XRD will show that the final product is in the form of a pure new phase, named SSZ-117x Boron and exhibits the characteristic peaks of Table 3.

[0086] Example 3

[0087] The as-synthesized boron SSZ-117x of Example 2 was heated in an excess of dimethylformamide at 150°C in a closed reactor for 5 days. The solid was washed to remove the solvent upon cooling and then washed with water and dried at 95°C. The mass loss from this extraction was 20%. The dried solid was then subjected to ozonolysis at 150°C overnight to remove any residual SDA in the pores. The open structure now had a substantially altered XRD pattern as shown in Table 4.

[0088] Table 4

[0089] <![CDATA[2-θ (a) ]]> d-spacing, nm <![CDATA[Relative strength (b) > 8.00 1.10 M 11.65 0.76 VS 18.8 0.47 M 21.8 0.41 M(width) 22.8 0.39 S

[0090] (a) ±0.30 degrees

[0091] (b) The powder XRD patterns provided are based on a relative intensity scale, where the most intense line in the X-ray pattern is assigned a value of 100: W = weak (>0 to ≤20); M = medium (>20 to ≤40); S = strong (>40 to ≤60); VS = very strong (>60 to ≤100).

[0092] Example 4

[0093] An as-synthesized sample of SSZ-117 with boron and Ge was treated with 10 cc of dimethylformamide / gm of zeolite at 150°C in a closed reactor for 3 days. The material was collected by filtration and then washed with water. After drying, the material (the xrd pattern of the material changed from SSZ-117 to 117x) was then treated with flowing ozone at 150°C overnight to complete the removal of the organics used to prepare the zeolite.

[0094] The material (0.825 g) was then treated in 12 ml of water with 0.128 g of 50% CsOH to neutralize any acidity. This treatment was carried out at room temperature for 25 hours and then filtered. The collected solid was then calcined in air to 300°C.

[0095] The calcined boron SSZ-117x was then redispersed in 18 ml of water with 0.0155 grams of tetraamine platinum chloride and stirred at room temperature for 24 hours. The material was then collected, calcined to 300°C and then pressed and sieved to 24 / 40 chips for loading into the reactor.

[0096] Example 5

[0097] Pretreatment of Catalytic Naphtha Reforming Catalysts

[0098] The catalytic naphtha reforming catalyst prepared in Example 4 was sulfided. The sulfidation reaction was carried out in a downflow fixed bed reactor system. The process is described as follows:

[0099] The catalyst was sieved to 24-40 chips and then loaded into the center of a stainless steel tubular reactor. The catalyst (0.6 g dry weight as determined by TGA (thermogravimetric analysis) at 1112°F) was first dried in a N2 stream (300 ml / min) at a heating rate of 10°F / min from room temperature to 400°F and held at 400°F for 30 minutes. To reduce the platinum in the catalyst, the catalyst was then heated in a H2 stream (300 ml / min) at a heating rate of 5°F / min from 400°F to 900°F and held at 900°F for 30 minutes. Finally, the catalyst was cooled down to 800°F to start the sulfidation reaction.

[0100] The feed applied for the sulfidation reaction is anhydrous n-octane containing 200ppm sulfur (as dimethyl disulfide).Sulfidation was carried out for 60 minutes at 800°F and atmospheric pressure.H2 and liquid feed flow rate are 30ml / min and 0.43ml / min respectively.After sulfidation, the catalyst is heated from 800 to 900°F in a few minutes in H2 stream (300ml / min) and then heated at 900°F for another 30 minutes to remove the excessive sulfur substances blocked in the hole and / or on the surface of the catalyst.Finally, the catalyst is heated and raised or cooled to the pre-set reaction temperature (e.g. 850 or 950°F) in 2 hours in the same H2 stream (300ml / min) to prepare the catalytic naphtha reforming test in Example 6.

[0101] Example 6

[0102] Catalytic Naphtha Reforming Test Process

[0103] Following the sulfidation procedure described in Example 5, the catalytic naphtha reforming reaction was carried out as described below.

[0104] The catalyst was heated up or cooled down to the preset reaction temperature (950°F for Example 8) in the same H2 flow (300 ml / min) over 2 hours to prepare for the start of the catalytic naphtha reforming test in this example (as described in Example 5). At the same time, the reactor system was pressurized to the preset pressure (150 psig for Example 8). At the same time, the H2 flow was adjusted to the preset rate (16 ml / min for Example 8). The feed rate was 1.75 ml / hour (for Example 8).

[0105] In the following examples, catalytic naphtha reforming experiments were conducted using the naphtha feed described in Example 7 at a hydrocarbon WHSV of 2.2 and a hydrogen to hydrocarbon molar ratio of 3.0.

[0106] Example 7

[0107] Feed for Catalytic Naphtha Reforming Test

[0108] GC analysis data from the feed for the catalytic naphtha reforming test are given in Table 5, along with GC results for its catalytic naphtha reforming test product from Example 8 over the catalyst described in Example 4. The GC data were obtained via on-line analysis.

[0109] Example 8

[0110] Products from catalytic naphtha reforming tests

[0111] The GC analysis data for the feed from Example 7 used in the catalytic naphtha reforming tests are given in Table 5, along with the results for its catalytic naphtha reforming test product from this Example over the catalyst described in Example 4. The catalytic naphtha reforming experiments were conducted at 950°F, 150 psig, a hydrocarbon WHSV of 2.2, and a hydrogen to hydrocarbon molar ratio of 3.0.

[0112] The GC results from the feed for the catalytic naphtha reforming test (Example 7) and the product from its catalytic naphtha reforming test (Example 8) over the catalyst described in Example 4 are shown below in Table 5. Reaction Conditions: 950°F, 150 psig, hydrocarbon WHSV of 2.2 and a hydrogen to hydrocarbon molar ratio of 3.0.

[0113] Table 5

[0114]

[0115]

[0116] As shown in Table 5, the products showed a large increase in aromatic compounds, which can be used for high octane gasoline. Boron SSZ-117x successfully reformed the feedstock of Example 7.

[0117] As used in this disclosure, the words "comprising" or "comprising" are intended to be open ended transitional, meaning the specified elements are included but not necessarily excluding other unspecified elements. The phrases "consisting essentially of" or "consisting essentially of" are intended to mean excluding other elements of any significance to the composition. The phrases "consisting of" or "consisting of" are intended to be transitional, meaning excluding all but the recited elements except for only minor trace impurities.

[0118] All patents and disclosures cited herein are incorporated herein by reference to the extent that they are not inconsistent with this article. It will be understood that some of the above-mentioned structures, functions and operations of the above-mentioned embodiments are not necessary for implementing the present invention, and are included in the description only for the completeness of one or more exemplary embodiments. In addition, it will be understood that the specific structures, functions and operations set forth in the above-mentioned patents and disclosures can be implemented in conjunction with the present invention, but they are not necessary for the implementation of the present invention. It should therefore be understood that the present invention can be implemented in a manner different from the specific description without actually departing from the spirit and scope of the present invention as defined by the appended claims.

Claims

1. Molecular sieves, in their as-synthesized form, having a powder X-ray diffraction pattern comprising the following peaks: And the molecular sieve contains boron.

2. The molecular sieve according to claim 1, having a composition comprising the following molar relationship: B2O3:(n)TO2 wherein n is ≥ 10; and T is a tetravalent element including silicon and germanium.

3. The molecular sieve according to claim 1, having a composition comprising the following molar relationship: B2O3:(n)TO2 wherein n is ≥ 15; and T is a tetravalent element including silicon and germanium.

4. The molecular sieve according to claim 1, having a chemical composition comprising the following molar relationship: wherein T is a tetravalent element including silicon and germanium; and Q - Contains the N,N,N,3,5-pentamethyladamantan-1-ammonium cation.

5. The molecular sieve of claim 4 which is sulfided and comprises a Group VIII metal.

6. The molecular sieve of claim 5, wherein the Group VIII metal is platinum or palladium.

7. A method for synthesizing the molecular sieve according to claim 1, the method comprising: (a) providing a reaction mixture comprising: (1) a FAU framework type zeolite having a SiO2 / Al2O3 molar ratio of at least 300; (2) Source of germanium; (3) Boron source; (4) N,N,N,3,5-pentamethyladamantane-1-ammonium hydroxide (Q); (5) a fluoride ion source; and (6) Water; (b) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the molecular sieve; and (c) Removal of Q from the molecular sieve framework.

8. The method according to claim 7, wherein the reaction mixture has the following composition in terms of molar ratio: Wherein T is a tetravalent element including silicon and germanium.

9. The method according to claim 7, wherein the reaction mixture has the following composition in terms of molar ratio: Wherein T is a tetravalent element including silicon and germanium.

10. The method of claim 7, wherein the FAU framework-type zeolite is zeolite Y or a post-synthetic modified form.

11. The method of claim 7, wherein the crystallization conditions include a temperature of 125°C to 200°C.

12. The process of claim 7, wherein the reaction mixture has a Q / F molar ratio in the range of 0.8 to 1.

2.

13. A method of converting a feedstock comprising an organic compound into a conversion product, the method comprising contacting the feedstock with a catalyst comprising the molecular sieve of claim 5 under organic compound conversion conditions.

14. A method of converting a feedstock comprising an organic compound into a conversion product, the method comprising contacting the feedstock with a catalyst comprising the molecular sieve of claim 6 under organic compound conversion conditions.

15. The method of claim 13, wherein the conversion reaction is reforming.

16. The method of claim 14, wherein the conversion reaction is reforming.

17. A method of ion exchanging metals, the method comprising contacting a stream comprising heavy metals with the molecular sieve of claim 4.

Citation Information

Patent Citations

  • MOLECULAR SIEVE SSZ-117x, ITS SYNTHESIS AND USE

    US20220072520A1